Peran International Justice Missions (IJM) dalam Menangani Kasus Online Sexual Exploitation of Children (OSEC) di Filipina pada tahun 2010-2019 - Devi, Anak Agung Ayu Krisna; Rainy Priadarsini, Ni Wayan; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
This study aims to analyse the role of International Justice Missions (IJM) in handling Online Sexual Exploitation of Children (OSEC) in the Philippines during the period 2010 to 2019 using qualitative-descriptive as research methods. Two concepts are used in this study, Cybercrime to identify OSEC as a crime involving computers and networks, and Civil Society Organizations (CSOs) to analyse IJM’s role by Rescuing and Restoring Victims, Bring Criminals to Justice, and Strengthening Justice Missions by being part of CSOs as an educator in educating the victims, the people, and the law enforcement of Philippines, a counterpart by collaborating with the government and the law enforcement, and an agenda setter by setting OSEC case as an important and crucial agenda for the government. IJM’s work in the Philippines is to help improving the Philippines’ Government and law enforcement in handling OSEC cases by conducting three programs in three areas. This study analysed the role of IJM as part of civil society by collaborating with the government and local NGOs in identifying and investigating OSEC cases to help in reducing the cases in the Philippines.